OPTIMALISASI PERAN KELUARGA, SEKOLAH DAN MASYARAKAT DALAM UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOBA DI DESA PUSAKA RAKYAT - Elfirda Ade Putri; Adi Nur Rohman (Abdi Bhara, 2023)
Drugs are needed for treatment and health services.However, if it is misused or used not in accordance with thestandard of treatment, especially if it is accompanied by illicitdrug trafficking, it will have very detrimental consequences forindividuals or society, especially the younger generation. Thenumber of drug abuse among students in 2022 (from 13provincial capitals in Indonesia) will reach 2.29 million people.One group of people who are prone to being exposed to drugabuse are those in the age range of 15-35 years or the millennialgeneration. The method used in the implementation of thisCommunity Service is the method of coaching and counseling inthe assisted villages, namely by conducting counseling andmentoring for families, schools and the community in LubangBuaya Village, Setu District. The purpose of implementing thisCommunity Service is to provide knowledge and understandingto the l